Analisis Kesalahan Berbahasa Tataran Ejaan dan Sintaksis pada Karangan Persuasi Mahasiswa Universitas Muhammadiyah Mamuju - Ayyub Ht, A. Muh.; Hamzar, Hamzar; Basri, Subianto (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
This research aims to seek language solecisms at spelling and syntax levels in the persuasive compositions of Muhammadiyah Mamuju University students. The sample for this article comprised 29 people who were determined using the purposive sampling technique. The researchers employed a qualitative content analysis method by portryaing written language errors. The data was collected using an observation technique and a written test where learners wrote persuasive treatises with the theme 'Education' which were then analysed for language mistakes by classifying their types that existed and then describing them qualitatively based on the sorts of inaccuracy found. From the results of this research, it could be seen that in all the collegians there were still errata made. Those were generally simple flaws but did not meet the required standards of the General Guidelines for Indonesian Spelling. Those tended to occur in the spelling aspects, especially when writing letters at the beginning of sentences that utilised lowercase letters where capital letters should be used. Apart from that, there were also errors in the use of capital letters in words that should be lower cases in the middle of a sentence and vice versa in the use of lower case letters that should be capital letters. Then, there were also informants who created errors due to an excess of the letter -h in the word mudah and a lack of the letter -e in the word prubahan. Additionally, there were also subjects who still produced errors in the syntactic aspects, in particular having hurdles in distinguishing di- as an affix (prefix) and di- as a preposition as well as writing the conjunction namun which were not correct at the beginning of the sentence.